E-learning QUICK checklist - Khan, Badrul Huda.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Ave., Hershey, PA, 17033, USA), 2005)
E-Learning QUICK Checklist walks readers through the various factors important to developing, evaluating and implementing an open, flexible and distributed learning environment. This book is designed as a quick checklist for e-learning. It contains many practical items that the reader can use as review criteria to check if e-learning modules, courses and programs provide the level of services that learners (or consumers) should expect.
Institutional -- Management -- Technological -- Pedagogical -- Ethical -- Interface design -- Resource support -- Evaluation.
"E-Learning QUICK Checklist is an abbreviated version of the IGI book, Managing E-Learning: Design, Delivery, Implementation and Evaluation, by Badrul Khan"--T.p. verso.
Includes bibliographical references (p. 213).
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on Sept. 10, 2010).
Keywords: Distance education -- Computer-assisted instruction -- Management; Web-based instruction -- Management; Internet in education; Electronic books